Anticancer effects of Ixeris dentata (Thunb. ex Thunb.) nakai extract on human melanoma cells A375P and A375SM. (24th December 2016) - Lee, Hae Nim; Shin, Seong Ah; Choo, Gang Sik; Kim, Hyeong Jin; Park, Young Seok; Park, Byung Kwon; Kim, Byeong Soo; Kim, Sang Ki; Cho, Sung Dae; Nam, Jeong Seok; Choi, Chang Sun; Jung, Ji Youn
Abstract: Ethnopharmacological relevance: The plant species Taraxacum coreanum (TC), Youngia sonchifolia (YS), and Ixeris dentata (ID) belong to the family Compositae and are used for medicinal purposes in traditional medicine. However, the anticancer effects of TC, YS, and ID extracts and the underlying molecular mechanisms in melanoma cells have not been elucidated. Aim of the study: To investigate the potential anticancer effects of TC, YS, and ID extracts on human melanoma cells and explore the potential pharmacological mechanisms in vitro and in vivo . Materials and methods: In this comparative study, we investigated the effects of TC, YS, and ID extracts on cell proliferation in human melanoma A375P and A375SM cells using MTT[3-(4, 5-dimethylthiazol-2-yl)−2, 5-diphenyltetrazolium bromide] assays. Apoptotic cells were detected by 4′, 6-diamidino-2-phenylinodole (DAPI) staining. We also investigated whether the growth-inhibitory effects were associated with the induction of apoptosis and whether the mechanisms of cell death were the result of signaling molecules such as p53, Bax, Bcl-2, caspase-9, Poly-ADP ribose polymerase (PARP), and Erk (Extracellular signal-regulated protein kinase) 1/2. The in vivo antitumor effects were evaluated by measuring the tumor volume and weight and performing Terminal deoxynucleotidyl transferase (TdT) dUTP Nick End Labeling (TUNEL) assay and immunohistochemistry (IHC) in tumor xenograft models. Results: TC, YS, and ID extracts effectively inhibited the growth of A375P and A375SM cells. In addition, several apoptotic events were observed following treatment, including DNA fragmentation and chromatin condensation by DAPI staining. The extracts increased p53, Bax, cleaved-caspase-9 and cleaved-PARP expression, whereas the expression of Bcl-2 was decreased in both cell lines. Furthermore, ID extract significantly inhibited the activation of Erk1/2 in both cell lines. Among the three extracts, ID had the strongest apoptotic effects. The administration of ID extract to mice inhibited tumor growth without any toxicity following 4 weeks of treatment. This extract increased the expression of apoptotic cells and p53 protein and decreased phospho-Erk1/2 protein. Conclusion: TC, YS, and ID extracts suppress the growth of human melanoma cells through apoptosis. Among these extracts, ID has the strongest anticancer and apoptotic effects. It induces apoptosis through the inhibition of Erk1/2 in A375P and A375SM human melanoma cells and in tumor xenograft models and may be a potential chemotherapeutic agent against melanoma. Graphical abstract: